2011
DOI: 10.1002/chem.201002659
|View full text |Cite
|
Sign up to set email alerts
|

Columnar Mesophases Based on Zinc Chlorophyll Derivatives Functionalized with Peripheral Dendron Wedges

Abstract: A chlorophyll derivative with a central zinc ion, a methoxy functionality at its 3(1)-position, and functionalized with a second-generation dendron (3,4-3,4,5)12G2-CH(2)OH at its 17(2)-position was synthesized starting from natural chlorophyll a (Chl a). This compound exhibits liquid crystalline (LC) behavior and its mesomorphic properties have been characterized by differential scanning calorimetry (DSC), polarisation optical microscopy (POM), powder X-ray diffraction (XRD), and scanning probe microscopy (SPM… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

1
27
0

Year Published

2012
2012
2016
2016

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 112 publications
1
27
0
Order By: Relevance
“…Therefore, the observed fibrils here may be of molecular columns lying on the substrate plane of the film. Actually, the similar fibril‐like structures have been reported previously in AFM observation in some other columnar LC systems 19, 20. Figure 2b is an AFM image of the same FCLC film taken at RT cooled after poling.…”
supporting
confidence: 84%
“…Therefore, the observed fibrils here may be of molecular columns lying on the substrate plane of the film. Actually, the similar fibril‐like structures have been reported previously in AFM observation in some other columnar LC systems 19, 20. Figure 2b is an AFM image of the same FCLC film taken at RT cooled after poling.…”
supporting
confidence: 84%
“…estimated an upper limit of 0.002 cm 2 V −1 s −1 for an ideally ordered solid‐state material of these dyes. Microwave‐conductivity experiments on a liquid‐crystalline zinc chlorin derivative performed by our research group showed charge mobilities exactly in this range 17…”
mentioning
confidence: 56%
“…So far, in contrast to the excellent excitontransport characteristics, [2,15] (bacterio-)chlorophyll dyes have not been demonstrated to possess outstanding charge-carriertransport properties. [17] In an identical experiment, the intrinsic charge-carrier mobility of zinc chlorin 1 in the solid state was characterized by the pulse-radiolysis time-resolved microwave conductivity (PR-TRMC) technique in the temperature range from À25 to 100 8C ( Figure S7 and Table S1). Microwaveconductivity experiments on a liquid-crystalline zinc chlorin derivative performed by our research group showed charge mobilities exactly in this range.…”
mentioning
confidence: 99%
“…Microwaveconductivity experiments on a liquid-crystalline zinc chlorin derivative performed by our research group showed charge mobilities exactly in this range. [17] In an identical experiment, the intrinsic charge-carrier mobility of zinc chlorin 1 in the solid state was characterized by the pulse-radiolysis time-resolved microwave conductivity (PR-TRMC) technique in the temperature range from À25 to 100 8C ( Figure S7 and Table S1). With this technique, a short pulse of high-energy electrons (10-50 ns, 3 MeV) generates a uniform concentration of charge carriers in the sample that is detected by a continuous source of microwaves.…”
mentioning
confidence: 99%